2023
DOI: 10.1108/ijoa-12-2022-3543
|View full text |Cite
|
Sign up to set email alerts
|

Does workplace toxicity undermine psychological capital (PsyCap) of the employees? Exploring the moderating role of gratitude

Abstract: Purpose This paper aims to examine the relationship between workplace toxicity and psychological capital (PsyCap). It also investigates the moderating role of gratitude in the toxicity–PsyCap link. Design/methodology/approach The study is based on explorative-cum-descriptive research design. The sample comprises 411 employees engaged in banking, insurance, IT, automobile and oil and gas companies. The collected data is explored for reliability, validity, multicollinearity and common method variance estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 174 publications
(181 reference statements)
0
3
0
Order By: Relevance
“…Gratitude can be considered an alternative to improve wellbeing in various situations, including organizational contexts. The incorporation of regular gratitude-based interventions within organizations can decrease workplace toxicity ( Mahipalan and Garg, 2023 ), and diminish turnover intentions while promoting a healthy work environment ( Garg et al, 2023b ). In educational institutions, gratitude can reduce the effect of teasing by enhancing student’s positive emotions ( Bansal et al, 2023 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Gratitude can be considered an alternative to improve wellbeing in various situations, including organizational contexts. The incorporation of regular gratitude-based interventions within organizations can decrease workplace toxicity ( Mahipalan and Garg, 2023 ), and diminish turnover intentions while promoting a healthy work environment ( Garg et al, 2023b ). In educational institutions, gratitude can reduce the effect of teasing by enhancing student’s positive emotions ( Bansal et al, 2023 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Further, gratitude was claimed as beneficial at workplace. In a sample of 411 employees, Mahipalan and Garg ( 82 ) reported that gratitude moderated the relationship between workplace bullying and psychological capital of employees. A study involving 112 female employees in India found that gratitude was linked to family enrichment ( 83 ), and to spiritual well-being and distress ( 84 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also explored the relationship between appreciation, technostress, and adopting a positive perspective among the students (Garg et al, 2023b). Furthermore, Mahipalan and Garg (2023) examined how toxic workplace environments affect employees' psychological capital, focusing on the potential moderating role of appreciation. Meanwhile, Mahipalan and Sheena (2019) investigated the spirituality of the workplace and subjective happiness among high school educators, highlighting the moderating function of appreciation.…”
Section: Gratitudementioning
confidence: 99%